Dye Sensitized Solar Cell Output Power Based on FTO Disposition Immersion Time in Papaya Leave Chlorophyll - Sari, Poppy Diana; Wijaya, I Made Anom Sutrisna; Wijaya, I Made Anom Sutrisna; Giriantari, Ida Ayu Dwi; Wartini, Ni Made; Hartati, Rukmi Sari (Journal of Electrical, Electronics and Informatics; Vol 7 No 1 (2023): JEEI (July 2023), 2023)
Dye-Sensitized Solar Cell (DSSC) is a dye-based organic solar cell as a photon absorber developed by Prof. Gratzel (1991). Natural dyes are a solution to replace synthetic dyes which are commonly used for DSSC because they are affordable, available in large quantities, environmentally friendly and sustainable. The aims of this study was to analyze the effect of immersion time on the disposition of flourine-doped tin oxide – Titanium dioxide (FTO-TiO2) in the natural dye chlorophyll on the current, voltage and power produced. Using papaya leaves extract with a direct gap energy of 2.428 Ev, FTO-TiO2 deposition was immersed in chlorophyll with 5 levels of immersion time and 3 groupings. Current and voltage measurements were made at the output of the DSSC prototype. Using the Solar Power Generation System, the output voltage (Voc) is 341.167 mV, the current (Isc) is 64.755 ?A and the output power is 1.49 x 10-5 w/cm2 at 60 hours of immersion.